The dish [videorecording (DVD)] - Silauro, Santo; Sitch, Rob, 1962-; Neill, Sam; Harrington, Kevin, 1959-; Long, Tom; Warburton, Patrick; Brown, Bille, 1952-2013; Moody, Genevieve; Kane, Tayler; Billing, Roy; McMartin, John (Archive collection., 2001)
Story telling how the biggest television event in history was almost not televised. Apollo 11 goes to the moon and the first step is to be televised around the globe. But right before the landing, the dish flatlines. Its up to the unconventional Aussie crew and the by-the-book NASA supervisor to work together to fix the dish before the landing occurs.